Emerging Concepts in Management - Ladouceur, Jean (Relations industrielles / Industrial Relations, 1969)
This article reviews "Emerging Concepts in Management" by Max Wortman and Fred Luthans.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z